Efeito de estímulos vibratórios aplicados na região plantar sobre o equilíbrio corporal de idosas - Wanderley, Fábio da Silva (2009)
Objective: To determine the effect of vibration stimuli with 100 Hz frequency, applied to the plantar region, the body balance in women aged less than 60 years. Method: We selected 30 women aged less than 60 years with lack of static balance measured by the test support Unipodal with eyes open. The participants were randomly divided into an experimental group and a control group. All subjects were evaluated by four additional tests: the test Unipodal support with eyes closed, the Time Up and Go test, the Functional Reach test adapted, and Static Posturography evaluated using the force platform. A study was conducted blind, and the evaluators did not know to which group subjects were. The subjects in the experimental group received vibration therapy applied directly in the plant with 100 Hz frequency and oscillation of 2 mm. We performed 24 sessions of vibration stimuli, applied by the same physiotherapist. We analyzed the changes of the average number of individuals by two-way ANOVA with Tukey test as post-hoc to the data showing normal, and for not presenting normality test was used to Friedman. The comparison of the averages of the groups, experimental and control, was done using the one-way ANOVA for data presented normal and Kruskal-Wallis test for those who did not show normality. Results: We found significant differences between experimental and control groups in the third assessment of the Functional Reach test adapted in the speed of oscillation of the center of anterior-posterior pressure with the eyes open and closed and the area of Oscillation of the center of pressure with eyes closed. In examining the three evaluations of the intervention group was found to improve body balance in the Functional Reach test adapted in the speed of oscillation of the center of anterior-posterior pressure with the eyes open and closed and the area of Oscillation of the center of pressure with eyes closed. In the control group there was no statistically significant difference in any of the tests. Conclusion: The vibration stimuli applied to the plantar region, with 100 Hz frequency, showed beneficial effects on body balance in women over 60 years, being more effective in postural control of anteriorposterior axis and during the deprivation of vision.